MODEL DESAIN WEB SELF-PACED LEARNING UNTUK MICROLEARNING DENGAN PENDEKATAN HIGH-FIDELITY PROTOTYPING - Kurniawan, Edi; Syafnur, Afdhal; Sirait, Zulkarnain; Alfiandi, Willy (Smart Education, 2025)
Abstract: Digital transformation in education drives the need for flexible learning methods such as self-paced learning with microlearning. However, its effectiveness is highly influenced by the platform's design quality. This research aims to develop and evaluate a web design model supporting microlearning-based self-paced learning using a high-fidelity prototyping approach. The research method adopts the Design and Construct phase of Design-Based Research (DBR), which includes the implementation of a functional high-fidelity prototype and usability testing. Usability testing was conducted using two methods: the System Usability Scale (SUS) with 40 real users (37 Participants and 3 Admins), and Heuristic Evaluation (HE) by 7 expert evaluators. The SUS test results indicated an excellent level of usability with a combined average score of 82.5, categorized as